2007
DOI: 10.3748/wjg.13.6172
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of erythropoietin against acute lung injury in a rat model of acute necrotizing pancreatitis

Abstract: RESULTS:The mean pleural effusion volume, calculated LW/BW ratio, serum IL-6 and lung tissue MDA levels were significantly lower in EPO groups than in ANP groups. No statistically significant difference was observed in either serum or tissue values of IL-2 among the groups. The level of tumor necrosis factor-α (TNF-α) and IL-6 and accumulation of ox-LDL were evident in the lung tissues of ANP groups when compared to EPO groups, particularly at 72 h. Histopathological evaluation confirmed the improvement in lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 22 publications
(37 reference statements)
3
25
0
1
Order By: Relevance
“…In agreement with this notion, previous studies have demonstrated that EPO attenuated pulmonary neutrophil accumulation in animals experiencing hyperoxic injury [30,31], ischaemia/reperfusion injury [33,34], endotoxemia [36,37], nonseptic shock [38], and acute necrotizing pancreatitis [32]. Markers of neutrophil infiltration such as malondialdehyde levels and myeloperoxidase activity in the lung tissue are also reduced as a result of EPO administration [30,32,37].…”
Section: Anti-inflammatory Properties Of Epo During Ali/ardssupporting
confidence: 60%
See 3 more Smart Citations
“…In agreement with this notion, previous studies have demonstrated that EPO attenuated pulmonary neutrophil accumulation in animals experiencing hyperoxic injury [30,31], ischaemia/reperfusion injury [33,34], endotoxemia [36,37], nonseptic shock [38], and acute necrotizing pancreatitis [32]. Markers of neutrophil infiltration such as malondialdehyde levels and myeloperoxidase activity in the lung tissue are also reduced as a result of EPO administration [30,32,37].…”
Section: Anti-inflammatory Properties Of Epo During Ali/ardssupporting
confidence: 60%
“…EPO appears to protect the integrity of the pulmonary epithelial and endothelial cells and to attenuate the associated pulmonary oedema and deterioration of pulmonary oxygenation function. Treatment with EPO has been proven beneficial in experimental ALI caused by hyperoxia [30,31], acute necrotizing pancreatitis [32], ischaemia/reperfusion [33,34], experimental sepsis induced by cecal ligation and puncture [35] or LPS [36][37], zymosan induced nonseptic shock [38] and tracheobronchial and pulmonary type II epithelial injury, following traumatic brain injury [39]. In these studies EPO has been found to interact with its receptor (EPO-R) to induce a range of pleiotropic cytoprotective actions.…”
Section: Erythropoietin and Ali/ardsmentioning
confidence: 99%
See 2 more Smart Citations
“…We report here that a single injection of pHBSP given intravenously to rats after the onset of resuscitation attenuated the renal dysfunction, liver injury, pancreatic injury and neuromuscular injury caused by severe HR in the anesthetized rat. There is evidence that EPO attenuates the degree of lung inflammation and injury caused by hyperoxic injury (20), ischemia-reperfusion (21) and acute necrotizing pancreatitis (22). We report here that pHBSP attenuated the degree of inflammatory cell infiltration, alveolar septal thickening and congestion in the lungs of rats subjected to HR.…”
Section: Discussionmentioning
confidence: 50%